Antiaromatic 1, 5‐Diaza‐s‐indacenes. (16th August 2021) - Hanida, Kensuke; Kim, Jinseok; Fukui, Norihito; Tsutsui, Yusuke; Seki, Shu; Kim, Dongho; Shinokubo, Hiroshi
Abstract: s ‐Indacene is a classical non‐alternant hydrocarbon that contains 12 π‐electrons in a cyclic π‐conjugation system. Herein, we report its nitrogen‐doped analogue, 1, 5‐diaza‐ s ‐indacene. 1, 5‐Diaza‐ s ‐indacenes were readily prepared from commercially available 2, 5‐dichlorobenzene‐1, 4‐diamine through a two‐step transformation consisting of a palladium‐catalyzed Larock cyclization with diaryl acetylenes followed by hydrogen abstraction. The thus obtained 1, 5‐diaza‐ s ‐indacenes exhibited distinct antiaromaticity, as manifested in clear bond‐length alternation, a forbidden HOMO–LUMO transition, and a paratropic ring current. As compared to the parent s ‐indacene, the 1, 5‐diaza‐ s ‐indacenes showed higher electron‐accepting ability owing to the presence of imine‐type nitrogen atoms. The 1, 5‐diaza‐ s ‐indacene core is effectively conjugated with the peripheral aryl groups, which enables fine‐tuning of the absorption spectra and redox properties. The two possible localized forms of 1, 5‐diaza‐ s ‐indacene were compared in terms of their energetic aspects. Abstract : 1, 5‐Diaza‐s‐indacenes (see structure) were synthesized and found to exhibit distinct antiaromaticity as manifested by pronounced bond‐length alternation, a forbidden HOMO–LUMO transition, and a paratropic ring current. As compared to the parent s‐indacene, the 1, 5‐diaza‐s‐indacenes showed higher electron‐accepting ability owing to the presence of imine‐type nitrogen atoms.